Aliphatic Biomarker Signatures of Crude Oil from Tarakan Subbasin, Tarakan Basin, North Kalimantan, Indonesia - Yulfi Zetra; R.Y. Perry Burhan; Maulida Fitriyyah; Zjahra Vianita Nugrahaeni (Geological Agency, 2023)
Organic geochemical studies of crude oil from Pamusian Field, Tarakan Subbasin, Tarakan Basin, North Kalimantan, have been done. Biomarker aliphatic hydrocarbon fractions were identified using a combined gas chromatography-mass spectrometer (GC - MS). Identified biomarkers consist of n-alkane groups, isoprenoids, bicyclic sesquiterpenoids, and pentacyclic triterpenoids. The most abundant aliphatic hydrocarbon biomarker is pristane followed by n-C19. The existence of n-alkanes shows a homologous (n-C16- n-C30) with a unimodal distribution type. The abundance of n-C19 is higher than other n-alkanes, supported by LHCPI value of 2.03, as an indicator of organic matter derived from microbial organisms. The amount of long chain n-alkanes (n-C25- n-C30) is almost the same as medium chain n-alkanes (n-C19 - n-C24) indicating the source of organic compounds is not only from microbial organisms, but also from terrestrial higher plants. The presence of 8β (H)-drimane compounds together with homodrimane shows the presence of bacterial input on the formation of oil from organic compounds. Ratio of Pr/Ph is 3.76, ratio of drimane/homodrimane is 1.058, ratio of Pr/n-C17 is 34.41, and ratio of Ph/n-C18 is 16.02 indicating the source of organic compounds came from terrestrial higher plants deposited in the oxic environment, and disposed to increase biodegradation. The CPI value is 0.95, and the highest amount of 17α (H), 21β (H)-hopane compounds suggest that Tarakan Subbasin oil was mature, and the source of organic compounds was derived from bacteria Keywords: Tarakan Basin, organic geochemistry, aliphatic hydrocarbon fraction, CPI